The Blue Egg Festival. Río Negro, Los Lagos Region, Chile [Fiesta del Huevo Azul. Río Negro, Región de Los Lagos, Chile] - Seperiza-Wittwer, A (Institute of Advanced Studies, University of Santiago de Chile, 2021)
The Blue Egg Festival is a festival held in the tenth region of the Lakes in Chile, in which it transcends the Mapuche worldview by safeguarding one of its most significant bird species such as the Mapuche Hen. This festival takes place under ritual activities and Mapuche culture, as well as gastronomy. The Mapuche chicken eggs, characteristic for their blue color in the shell, are an immense treasure of this culture and are highly appreciated by locals and foreigners due to their great nutritional value. The objective of this work is to evoke the most important activities carried out in the framework of the festival, as well as to promote the preservation of the Mapuche culture through the massification of their culture. In the same way, economic activities and projects around the celebration of the Blue Egg Festival are rescued. © 2021 The Authors. Published by IASE.